Determinants of school teachers’ Organizational Citizenship Behaviors (OCBs) - Mat, Norsiah; Selamat, Sarah Mardhiah (2013)
This study examined the relationship between intrinsic and extrinsic motivation on organizational citizenship behaviors (OCBs) among secondary school teachers within the context of Malaysia.Drawing on a survey using a representative sample of 80 secondary school teachers selected through simple random sampling technique, the results showed that intrinsic motivation was positively influenced teachers’ OCB, while extrinsic motivation was not.The implications for further research was highlighted.